PSIII-5 Late-Breaking: Genetic Evaluation of Energy Efficiency in Bos taurus Cows Classified by Residual Feed Intake. (22nd October 2022) - Schaff, Nathan; Dafoe, Julia; Boss, Darrin L; Thomson, Jennifer M; Boles, Jane A
Abstract: Genetic selection for efficiency traits is essential to improve the profitability and sustainability of livestock operations. Inefficient metabolism and energy production in animal physiology leads to excess feed consumption, resulting in higher feed costs. The objective of this study was to investigate hepatic gene expression in mature Angus-influenced cows that were classified as low or high RFI as heifers and had either a low or high ratio of calf weaning weight to mature body weight at weaning. Eleven cows were selected from the Northern Agricultural Research Center (NARC) research herd. Cows were ranked as efficient (n = 5) or inefficient (n = 6) based on their low or high residual feed intake (RFI) measured as a growing heifer and then by the ratio of calf weaning weight by mature body weight. Animals were partitioned from the bottom quartile with low RFI as a heifer and weaned with a higher proportion of the calf were classified as efficient, and animals from the top quartile with a high RFI as a heifer and a lower ratio of the calf to body weight were classified as inefficient. Liver samples were collected by needle biopsy approximately one week after weaning and snap frozen. The liver gene expression profile was measured using RNAseq. Two cows' data were not reported, one from each group, as RNA quality prevented sequencing (Efficient n = 4 and Inefficient n = 5). Over 5 million reads were mapped for each sample and were aligned to BTau 4.6.1 reference sequence using HISAT2. Differentially expressed genes were determined using the DEseq2 R package using a model based on the negative binomial distribution, and p-values were adjusted using the Benjamini-Hochberg approach. A corrected P-value of less than 0.05 defined a differentially expressed gene. Gene lists were used for gene ontology and KEGG pathway enrichment using clusterProfiler software. One novel gene was significantly differentially expressed with higher expression in the efficient group. However, no annotation currently exists for this gene. Additionally, the KEGG pathway biosynthesis of unsaturated fatty acids was significantly enriched (P < 0.05) with the following differentially expressed genes SCD, FADS1/2, ELOVL6, and HACD2, all being down-regulated in inefficient cows. The enrichment of this pathway is most functionally relevant, as it indicates that local liver changes could directly affect the efficient metabolism and biosynthesis of fatty acids. With encouraging, but limited results, this study provides the groundwork for future study of the heritable mechanisms contributing to the generation of more energy-efficient cows.